2016
DOI: 10.1128/genomea.00668-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Sphingobium sp. Strain TCM1 and Sphingomonas sp. Strain TDK1, Haloalkyl Phosphate Flame Retardant- and Plasticizer-Degrading Bacteria

Abstract: Sphingobium sp. strain TCM1 and Sphingomonas sp. strain TDK1 are haloalkyl phosphate flame retardant- and plasticizer-degrading bacteria. We report here the draft genome sequences of these strains to provide insights into the molecular mechanism underlying their degradation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Among these CDSs, 2388 (63.87%) genes were classified into clusters of orthologous group (COG) families comprised of 23 categories (Table S2). The genome size of LK11 falls within the expected range (based on other genomic studies) and a varying number of plasmid has been observed in other strains (Gai et al 2011a ; Kera et al 2016 ; Li et al 2016 ; Miller et al 2010 ; Pan et al 2016a ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Among these CDSs, 2388 (63.87%) genes were classified into clusters of orthologous group (COG) families comprised of 23 categories (Table S2). The genome size of LK11 falls within the expected range (based on other genomic studies) and a varying number of plasmid has been observed in other strains (Gai et al 2011a ; Kera et al 2016 ; Li et al 2016 ; Miller et al 2010 ; Pan et al 2016a ).…”
Section: Resultssupporting
confidence: 65%
“…Recent studies have also demonstrated the role of Sphingomonas spp. in the degradation of organic chemical compounds, such as bisphenol (Fujiwara et al 2016 ), phenol (Gong et al 2016 ), triclocarban (Mulla et al 2016 ), phenanthrene (Liu et al 2016 ), chlorogenic acid (Ma et al 2016 ), nonylphenol polyethoxylates (Bai et al 2016 ), astaxanthin (Ma et al 2016 ), dioxin (Miller et al 2010 ), γ-hexachlorocyclohexane (Tabata et al 2013 ), nicotine (Zhu et al 2016 ), plasticizers (Kera et al 2016 ), and hexachlorocyclohexane isomers (Kumari et al 2002 ) among others. In addition to these degradation abilities, the Sphingomonas genus can also produce bioactive metabolites, such as indole acetic acid, gibberellins, sphingan (Li et al 2016 ), and gellan gum (Gai et al 2011b ).…”
Section: Introductionmentioning
confidence: 99%
“…strain TCM1 were determined to be EFVTQSDQRPP. We performed a Blast search against the draft genome of strain TCM1 20 using this N-terminal sequence as the query sequence and the putative gene (locus_tag A7Q26_24300) was found. However, no Shine-Dalgarno (SD) sequence was found around the putative translation initiation codon.…”
Section: Resultsmentioning
confidence: 99%
“…The OPs used in our MIX treatment are proven to be degradable and hence can be used as a resource for bacteria (Leahy and Colwell, ; Takahashi et al ., , , , ; Seo et al ., ; Abe et al ., , ; Joye et al ., ; Kera et al ., ; Vila‐Costa et al ., )). Yet, our study showed notably negative effects on bacterial growth of hydrocarbons and OPEs supplied at environmentally relevant concentrations.…”
Section: Discussionmentioning
confidence: 99%